Analysis of Mortality Improvement on the Pension Cost Due to Aging Population (MATEMATIKA, 2020)
Aging is a good indicator in demographic and health areas as the lifespanof the elderly population increases. Based on the government’s Economic Outlook 2019,it was found that an aging population would increase the government pension paymentsas the pensioners and their beneficiaries have longer life expectancy. Due to mortalityrates decreasing over time, the life expectancy tends to increase in the future. Theaims of this study are to forecast the mortality rates in the years 2020 and 2025 usingthe Heligman-Pollard model and then analyse the effect of mortality improvement onthe pension cost (annuity factor) for the Malaysian population. However, this studyonly focuses on estimating the annuity factor using life annuities through the forecastedmortality rates. The findings indicated that the pension cost is expected to increase ifthe life expectancy of the Malaysian population increases due to the aging population inthe near future. Thus, to reduce pension costs and help the pensioners from insufficientfinancial income, the government needs to consider an extension of the retirement age infuture.